A Dust Flow Separator Type Electrostatic Precipitator for Diesel Engine Particulate Matter Control - Colenbrander, John W. (My University, 2005)
Increasingly stringent legislation governing the emissions of diesel engine particulate matter (DPM) has required the development of technological improvements to diesel engines, fuels and exhaust treatments. A main focus of diesel particulate matter abatement is on exhaust after treatment, that consists of the removal of particulate matter from the exhaust gas after it exits the engine. This is currently accomplished with regenerative diesel particulate traps that are effective at removing DPM, but are costly and introduce a significant pressure drop in the exhaust flow.
The objective of this study was to evaluate the potential of a novel particulate removal system consisting of a particulate flow separator combined with electrostatic precipitators (ESPs). Previous application of this system to natural gas emissions resulted in collection efficiencies larger than 90% with negligible pressure drop.
The ESPs used in the proposed flow separator-ESP were characterized and have collection efficiencies of up to 99% at the flow rates studied. The flow separator-ESP was characterized with a straight inlet section and an expanding inlet section. The collection efficiency of the flow separator-ESP configured with the expanding inlet section was up to 60% for a flow rate of 2.5 kg/hr, that corresponded to laminar flow with Reynolds number of 1100. Collection efficiencies on the order of 20% were obtained for exhaust flow rates of 3.75 kg/hr (Re = 1500) and 5.0 kg/hr (Re = 2100) for both inlet configurations, and 2.5 kg/hr with the straight inlet. The effectiveness of the current design is limited by exhaust flow rate.
The diesel exhaust gas was sampled using a partial flow dilution tunnel developed specifically for this study. The dilution ratio for this system can be estimated to within ±10% using volumetric flow measurements. It was found that changes in the dilution and sampling velocity ratios for diesel exhaust have some effect on measured particulate matter mass concentrations.
Keywords: dust flow, separator type, electrostatic precipitator, diesel engine, particulate matter control